Mucosa-Associated Lymphoid Tissue Lymphoma of the Pituitary Gland: MR Imaging Features - Lee, Jeong Hyun; Lee, Ho Kyu; Choi, Choong Ton; Huh, Jooryung (American Journal of Neuroradiology, 2002)
Summary: We report the MR features in a previously healthy patient with mucosa-associated lymphoid tissue lymphoma of the pituitary gland. The MR images showed a homogeneously enhancing solid mass in the sellar region and both parasellar regions; this mass extended through the bilateral foramina ovale along the third branches of the trigeminal nerves. The mass completely encircled the cavernous segments of both internal carotid arteries without narrowing the lumen. Gadopentetate dimeglumine–enhanced T1-weighted MR images showed homogeneous, strong enhancement of the mass.